Cosmetic Surgery and Body Dysmorphic Disorder – An Update() - Higgins, S. (Int J Womens Dermatol, 2017)
With the increasing volume and popularity of cosmetic procedures and surgeries, physicians in related specialties are increasingly likely to encounter patients with body dysmorphic disorder. Given the ethical, safety, and legal considerations involved in aesthetic procedures in these patients, accurate identification and appropriate selection for procedures is crucial.